THE EFFECT OF FINANCIAL INCENTIVES SCHEME TOWARD INTENTION TO DISCLOSE FRAUD - Kartika, Ikhsanti Dian; Sari, Ratna Candra (Universitas Negeri Yogyakarta, 2019)
Abstract : The Effect of Financial Incentives Scheme toward Intention to Disclose Fraud. The purposes of this research is to examine the effect of financial incentive scheme toward intention to disclose fraud. This research is an experimental research using experimental factorial design 1x1 between subject. The population of this study was 81 Undergraduate Accounting Students of the Faculty of Economics, Yogyakarta State University, year 2016. Validity test using Face Validity. The research hypothesis was processed using a One-Way ANOVA statistical test.The result of this research showed that there is an effect of financial incentives scheme on the intention to disclose fraud with a significance value of 0.000. Keywords : Financial Incentives Scheme, Disclosing Fraud, Whistleblowing